The institutional & administrative basis of coastal zone and fisheries management in Trinidad & Tobago - Soomai, Suzette (2005)
Suggests the importance of consolidating all sectoral components of coastal zone planning under one umbrella and the establishment of an adequately funded and dedicated administrative unit to develop this area. Sees the need to enact appropriate legislation to govern the coastal zone. Opines that efforts must also be made to conduct interdisciplinary research to guide the management of coastal and fisheries resources and to ensure the well being of coastal communities.